2011
DOI: 10.1051/0004-6361/201117294
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic shear covariance: the log-normal approximation

Abstract: Context. Accurate estimates of the errors on the cosmological parameters inferred from cosmic shear surveys require accurate estimates of the covariance of the cosmic shear correlation functions. Aims. We seek approximations to the cosmic shear covariance that are as easy to use as the common approximations based on normal (Gaussian) statistics, but yield more accurate covariance matrices and parameter errors. Methods. We derive expressions for the cosmic shear covariance under the assumption that the underlyi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
150
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 106 publications
(156 citation statements)
references
References 61 publications
5
150
0
Order By: Relevance
“…Indeed, as Kayo et al (2001) have shown, the distribution of the density fluctuations in the universe can rather well be described by a log-normal distribution. Moreover, Taruya et al (2002) and Hilbert et al (2011) have shown that the same holds true for the cosmic shear convergence field, which serves as justification for using these particular non-Gaussian fields for our study. Furthermore, Hilbert et al (2011) employed the log-normal ansatz to calculate the covariance of the power spectrum of cosmic shear fields; they showed that this model provides fairly accurate results, when compared to ray-tracing simulations.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…Indeed, as Kayo et al (2001) have shown, the distribution of the density fluctuations in the universe can rather well be described by a log-normal distribution. Moreover, Taruya et al (2002) and Hilbert et al (2011) have shown that the same holds true for the cosmic shear convergence field, which serves as justification for using these particular non-Gaussian fields for our study. Furthermore, Hilbert et al (2011) employed the log-normal ansatz to calculate the covariance of the power spectrum of cosmic shear fields; they showed that this model provides fairly accurate results, when compared to ray-tracing simulations.…”
Section: Introductionsupporting
confidence: 59%
“…Moreover, Taruya et al (2002) and Hilbert et al (2011) have shown that the same holds true for the cosmic shear convergence field, which serves as justification for using these particular non-Gaussian fields for our study. Furthermore, Hilbert et al (2011) employed the log-normal ansatz to calculate the covariance of the power spectrum of cosmic shear fields; they showed that this model provides fairly accurate results, when compared to ray-tracing simulations. However, we caution that the log-normal approach has yet not been shown to give a realistic approximation for higher-order correlation functions and that the log-normal is not completely determined by its moments (Coles & Jones 1991;Carron & Neyrinck 2012).…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…-The assumption of Gaussian statistics for the cosmic shear fields is inaccurate for nonlinear scales (roughly ten arcmin or smaller), which leads to an underestimation of the shear noise covariance (Semboloni et al 2007;Hartlap et al 2009;Hilbert et al 2011). The adopted log-normal statistics (Bouchet et al 1993) of the galaxy clustering, on the other hand, is presumably a good approximation of the galaxygalaxy lensing and galaxy clustering covariance.…”
Section: Simulated Noise Covariancementioning
confidence: 99%